Quality of government for environmental wellbeing? Subnational evidence from European regions - Andrea Vaccaro; Carlotta Montorsi; Chiara Gigliarano (Regional Studies, Regional Science)
This study investigates the relationship between quality of government and environmental wellbeing in European regions at the NUTS-2 level. First, we find that subnational environmental data are spatially interdependent. Then, we construct a set of composite indicators of environmental wellbeing via Bayesian spatial factor analysis. Finally, by using these composite indicators in spatial regression analysis, we show that institutional quality is a key determinant of environmental wellbeing. We also find that the institutions-environment nexus varies across dimensions of environmental wellbeing – institutions matter especially for the quality of air and soil. Policymakers should be aware that environmental degradation can be tackled by building more effective and well-functioning regional public institutions.